2017
DOI: 10.1103/physrevb.96.104516
|View full text |Cite
|
Sign up to set email alerts
|

Onset of surface superconductivity beyond the Saint-James–de Gennes limit

Abstract: We revisit the problem of the surface superconductivity nucleation focusing on the detailed study of the critical field H c3 as a function of temperature and disorder. Using the semiclassical Eilenberger formalism we find that away from the Ginzburg-Landau region the ratio between the nucleation critical field H c3 and the upper critical field H c2 deviates strongly from the Saint-James-de Gennes limit. In particular, the H c3 /H c2 is found to be a nonmonotonic function of temperature, which reaches the maxim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…2(d). The fact that the voltage probes are of finite size, 5 µm in this experiment, we argue that these anomalous oscillation effects may well be the Aharonov-Bohm interference effect predicted theoretically 9,23 . For clarity, the anti-symmetric (Hall effect) and the symmetric (resistive) parts of R xy data in Fig.…”
Section: Resultssupporting
confidence: 57%
“…2(d). The fact that the voltage probes are of finite size, 5 µm in this experiment, we argue that these anomalous oscillation effects may well be the Aharonov-Bohm interference effect predicted theoretically 9,23 . For clarity, the anti-symmetric (Hall effect) and the symmetric (resistive) parts of R xy data in Fig.…”
Section: Resultssupporting
confidence: 57%
“…The nucleation of superconductivity on surface becomes more pronounced when the applied magnetic field is parallel to the sample. In such case, the vortex lattice overlaps cause the nucleation of the superconductivity to the surface [19]. Further, for type II superconductors the pair breaking is caused either by spin paramagnetic or orbital effect.…”
Section: Transport Measurementsmentioning
confidence: 99%
“…Vortex cores extend beyond due to the thickness of the vortex lattice, which leads to the nucleation at the surfaces of the superconductor. This nucleation gives rise to Saint-James–de Gennes (SJdG) phase of the surface, which exists at even higher parallel field Hc3 [104]. In fact, SJdG showed that superconductivity can nucleate at a metal–insulator interface in a parallel field Hc3 higher by a factor of 1.695 than Hc2 [105,106].…”
Section: Applications To Bulk Superconductormentioning
confidence: 99%
“…In his seminal work, Abrikosov showed that the relation Hc3=1.695Hc2 is satisfied only over the entire range of temperatures below T c [107]. In [104], the authors found that SJdG relation is a non-monotonic function of temperature. The ratio Hc3/Hc2 reaches a maximum close to 2 for a set of parameters corresponding to a crossover region from ballistic to diffusive scattering in the bulk of the superconductor.…”
Section: Applications To Bulk Superconductormentioning
confidence: 99%